Invasive pulmonary and sino-orbital mucor mycosis in patient with SARS-Cov-2 infection with diabetic ketoacidosis - Singla, Neeraj; Agrawal, Suraj; Bhankhur, Dimpi (International Journal of Advances in Medicine, 2021)
Patients with Severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) are susceptible for developing fungal infection due to uncontrolled diabetes or immunosuppression. A 46 years male presented with diabetic ketoacidosis, respiratory failure with peri orbital blackish discoloration with SARS-Cov-2 positive report. Computed tomography (CT) chest was suggestive of perihilar ground glass opacity and multiple thick-walled cavities. Left nasal cavity scrapings revealed hyaline aseptate hyphae and growth of Rhizopus arrhizus. Patient was initially managed conservatively with liposomal amphotericin B but later underwent orbital exenteration and finally succumbed. We want to emphasize higher mortality and aggressive management of mucor mycosis when it occurs with SARS-Cov-2 as a concurrent illness.